How to win in FIFA World Cup Qatar 2022? A study on the configurations of technical and tactical indicators based on fuzzy-set qualitative comparative analysis - Yan, Weihua; Li, Shiyue; Wang, Di; Yuan, Bo; Zeng, Haocheng; Ren, Dingmeng (Frontiers in Psychology, 2024)
FIFA World Cup, which represents the highest level in football, is regarded as a showcase to unfold the development trend of modern football, thus arousing great interest among researchers. However, most of previous research designs studied the simple linear correlation between technical indicators and game outcomes, which may overlook complex causality in football performance. The aim of current study was to introduce a new method to examine winning patterns emerging from Qatar 2022 through configurational lens. To this end, Fuzzy-set Qualitative Comparative Analysis (fsQCA) was conducted using 98 samples (n=98) out of 49 Qatar 2022 matches discriminating winning and losing teams in regular time (group stage) and in 30-minute extra time (knockout stage). Then we selected 7 variables as our causal conditions, namely, on target, possession, defensive line breaks, crosses, receptions in the final third, forced turnovers, and direct pressures. Necessity analysis and sufficiency analysis of configurations were conducted according to fsQCA requirements. The fsQCA operation showed that no individual causal condition is necessary to winning the game and 4 configurations are derived from QCA result and these combinations of conditions can fall into 3 typologies of play style: possession play style, direct play style and all-round play style. The result confirmed the fact that football is a complex system and suggested that the winning outcome is often produced by combinations of multiple factors. The findings of current study contribute to literature by introducing configurations of various technical and tactical indicators that could raise the possibility of winning and can be used by practitioners working within the fields of player development, coaching and match preparation.